Metabolic Effects of Ozone Therapy in Restorative Treatment of Patients with 1st Degree Arterial Hypertension - o’g’li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2023)
The effect of ozone therapy on the metabolic status of patients with arterial hypertension was studied. Positive changes in metabolic parameters were noted in patients with arterial hypertension after a course of treatment with medical ozone. Ozone therapy helps normalize metabolic processes in most patients, lipid and carbohydrate metabolism, and reduces the risk of atherogenic changes in the body.